Human and Civilizational Aspects of Islamic Values in Human Rights - Talal Agil Alkhiri (IAIN Ponorogo, 2022)
This research discussed Islamic education, civilizational values, and the relevance to human rights. This research used the library research method. The results of this research were divided into two parts. The first part provided a conceptual framework of values and their relation to people and civilization. The second part discussed eight examples of civilizational and human values of human rights in Islam. These eight values included tolerance, peace, freedom, Shura (mutual consultation), justice, equality, labor, and tolerance. In general, it concluded that Islam ensured people get to know one another within a perfectly controlled system that warrants human rights and conditions of happiness and purposeful human existence on earth. These values stem from the sources of Islam and the true Islamic vision of man, the universe, and life.